BSCI-18. Identifying novel drivers of lung-to-brain metastasis through in vivo functional genomics. (9th August 2021) - Aghaei, Nikoo; Lam, Fred C; Kasper, Ekkehard; Venugopal, Chitra; Singh, Sheila
Abstract: Introduction: Brain metastases, the most common tumors of the central nervous system, occur in approximately 20% of primary adult cancers. In particular, 40% of patients with non-small cell lung cancer develop brain metastasis. As systemic therapies for the treatment of non-small cell lung cancer become increasingly effective at controlling primary disease, patients are ironically succumbing to their brain metastases. This highlights a large unmet need to develop novel targeted therapies for the treatment of lung-to-brain metastases (LBM). We hypothesize that an in vivo functional genomic screen can identify novel genes that drive LBM. Methods: To do this, we developed a patient-derived xenograft (PDX) mouse model of LBM using patient lung cancer cell lines. This PDX model of LBM enables the use of fluorescent and bioluminescent in vivo imaging to track the progression of lung tumor and brain metastases. Results: We have performed an in vivo genome-wide CRISPR activation screening to identify novel drivers of LBM. We will derive candidate genes through mouse brain and lung tissue sequencing after mice reach endpoint. Expected Area of findings: This platform will lead to potential therapeutic targets to prevent the formation of LBM and prolong the survival of patients with non-small cell lung cancer. Limitations: There may be limitations in getting candidate hits that overlap in all mice in our first replicate. This can be remedied by conducting the in vivo screen in at least three biological replicates. Conclusion: To the best of our knowledge, this is the first genome-wide in vivo CRISPR activation screen searching for drivers of LBM using a PDX animal model. This study can provide a framework to gain a deeper understanding of the regulators of BM formation which will hopefully lead to targeted drug discovery.